PENGEMBANGAN RPP DAN LKS MATEMATIKA DENGAN MODEL PROBLEM BASED LEARNING PADA MATERI ARITMATIKA SOSIAL KELAS VII SMP/MTs - Alfe Rio Ignatius Simarmata; Sehatta Saragih; Kartini Kartini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The background of this research is the restrict of mathematics learning device as supporting learning referring to 2013 Curriculum. This research aims to develop the lesson plan and students worksheet of mathematics based on 2013 Curriculum with application of problem based learning on the subject social arithmetic for 7th grade students of Junior High School . Lesson plans and student worksheet are developed to structured in accordance with the steps of the scientific approach that is observing, questioning, reasoning, trying, and communicating. This study method used is 4D model that consist of define, design, development, and disseminat. Becaused of time and cost, the study was only to development step. Learning device that had been developed then validated by three validators and revised based on the input from validators. The valid students worksheet then tested in two stages, the small group trial with subjects are five students of class VII SMP Negeri 1 Lubuk Batu Jaya and large group trial with subjects are 22 students of class VII A SMP Negeri 1 Lubuk Batu Jaya. Based on the data analysis and discussion can be concluded that the lesson plan and students worksheet of mathematics based on 2013 Curriculum with application of problem based learning on the subject social arithmetic are valid with an average value for the lesson plan is 3.86 and the average value for student worksheet is 3.84, and is practical to use by 7th grade students.Keywords: Validity and Practicality, Research and Development, Problem Based Learning, Social Arithmetic